The Impact of Maritime Culture Assimilation on the Architecture of Gili Iyang Communities - Yusran, Yusfan Adeputera; Hilmy, Ayu Nur Izzati; Kusdiwanggo, Susilo (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2025)
Indonesia's cultural diversity provides a unique backdrop for understanding the dynamics of cultural assimilation, especially on Gili Iyang Island in Sumenep, Madura, where migration has shaped social and architectural aspects. This study explores the influence of cultural adaptation on architecture among the Bugis-Makassar, Buton-Binongko, and Sumenep-Madura communities on Gili Iyang Island. Utilizing a case study method, this research focuses on how these maritime-oriented communities adjust and modify architectural aspects in response to cultural interactions. The findings indicate that the assimilation affecting the architecture of Gili Iyang Island includes: (1) spatial organization and division from east to west and north to south, reflecting a balance between gender aspects and spiritual symbolism; (2) color concepts based on natural elements such as brown (earth), green (sea), blue (sky), and red-orange (fire); (3) ornaments inspired by the surrounding environment including plants, animals, and repetitive geometric patterns; (4) courtyards serving as the focal points for orientation and transition between buildings; (5) buildings that are closely spaced